Lisboa, Metrópole policêntrica e fragmentada - Salgueiro, Teresa Barata (1997)
TRENDS OF POLICENTRISM AND FRAGMENTATION IN LISBON - In this paper, we study the transformations of the spatial organisation of the Lisbon Metropolitan Area. The main focus is on the present restructuring dominated by three main processes. Firstly descentralisation of housing and economic activities, secondly development of new centralities, high status areas with very good accessibility and great attractivity, mainly occupied by office buildings or mixed-used developments (offices, retail, hotel, luxury apartments) in the inner city or close to new suburban highways; and, finally, selective gentrification and re-use of the central city, either by high income housing or modern services.The evolution outlined can achieve the replacement of a strong centralised metropolis with uequal distribution of employment and services between metropolitan core and suburban rings by a new multicentered structure. This evolution goes along with the transmition from the industrial to the post-industrial city that brings fragmentation of the socio-spatial structure with a juxtaposition of territories. In the economic sense the city loses its functional unity made of interdependent spacialised territories. In the social sense this reflects the rise in the number and differentiation due to the increase of opportunities and choices once the position in the labor market is no more sufficient to define social position and people look for and build their identification through goods, places and their symbols.